West African crop breeding programme launched - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A five-year programme to improve the basic food crops of Africa will start later this year. It aims to encourage the development of new strains of sorghum, millet, African rice cowpea, winged bean, mung bean, cassava, sweet potatoes and yams. The...